1993
DOI: 10.1007/bf00018797
|View full text |Cite
|
Sign up to set email alerts
|

Dunaliella salina from saline environments of the central coast of Peru

Abstract: An evaluation of the algal flora of the Salinas de Huacho on the coast of Peru between 1984 and 1990 was carried out by collection of algal mats and natural waters from a variety of habitats and by microscopic examination. D. salina occurred in lagoons and pools with a salinity range of 165x, to 350x, and formed planktonic and benthic communities. The benthic palmelloid stage of D. salina was found at higher salinities. Aplanospore formation was also observed. Associated halophilic species included D. viridis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
(8 reference statements)
1
5
0
1
Order By: Relevance
“…D. salina has the ability to grow over an extremely wide range of salinity from less than sea water to NaCl saturation (Montoya and Olivera, 1993 ). The normal cells of D. salina are ellipsoid to fusiform, without cell wall, but covered with mucilaginous glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…D. salina has the ability to grow over an extremely wide range of salinity from less than sea water to NaCl saturation (Montoya and Olivera, 1993 ). The normal cells of D. salina are ellipsoid to fusiform, without cell wall, but covered with mucilaginous glycocalyx.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that high salinity triggers palmella formation in D. salina (Montoya and Olivera, 1993 ), but the molecular mechanism of palmella formation is still unknown. Previous studies mainly focus on the mechanism of remarkable salinity and osmotic adaptability of D. salina .…”
Section: Introductionmentioning
confidence: 99%
“…In D. salina , such aplanospores contain canthaxanthin as the main carotenoid rather than β-carotene found in the vegetative cells [ 15 ]. In a study of D. salina from saline environments of the central coast of Peru, formation of spherical, reddish aplanospores were observed when collected plankton samples were kept in the laboratory for a few days [ 31 ]. In Great Salt Lake, round cyst-like cells of D. salina increased in numbers, especially on the bottom, when the temperature decreased below 0°C [ 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…Palmelloid benthic forms were seen mainly in winter at depths up to 1 m as irregular and lobulated clusters up to 3 mm in diameter. Nutrient deficiency, low temperature and low salinity may trigger the production of these palmelloid forms [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…La particularidad de estos ecosistemas como las lagunas costeras con fluctuaciones hídricas y de salinidad ha favorecido la presencia y en algunos casos la dominancia de especies tolerantes a condiciones extremas como el estrés salino (Montoya & Golubic 1991;Montoya, 2009;MINAM, 2015). En el Perú, estudios sobre la flora microalgal fitoplanctónica en ecosistemas acuáticos costeros salinos y salobres han sido realizados por Maldonado (1943), Chacón (1980), Montoya & Olivera (1993), Montoya (2009) y Montoya et al, (2006Montoya et al, ( , 2012.…”
Section: Introductionunclassified